Geografia e linguagem cinematográfica: análises e contribuições para o estudo de práticas de (in) justiça no espaço brasileiro - Rodrigues, Maria dos Anjos Pereira (2024)
This research was developed in the Postgraduate Doctorate course at the Federal University of Uberlândia-UFU, at the Institute of Geography, and its general objective is to analyze how Geography, with the contribution of cinematographic language, can contribute to socio-spatial understanding regarding justice in a regional and national context. The theme of justice is included in the analysis perspective of this research as an egalitarian element for all citizens, whether in solving problems in the regional or national context. In the quest to exercise justice as a principle of equality, judicial errors are perceived in the cases present in the two film narratives, the focus of analysis on the topic. With these prerogatives, the specific objectives developed were: to understand the historical and geographical formation of the Triângulo Mineiro Region; analyze cinematographic language from the perspective of cultural representation on the theme of justice; show, through analysis of the film “The Case of Irmãos Naves”, how the theme of Justice still remains a challenge in the regional context; and analyze the film “Federal Police: The law is for everyone”, to relate the theme of Justice from a national perspective. The aim is to contribute to the construction of a critical view of these filmic works, given that access to filmic works of different genres can constitute an analytical contribution to research in Geography. In this sense, with the development of a closer look to understand the semantics that the author (director or screenwriter of the film) wanted to express in his work; show, through images, the various contexts of society and consequently the geographic space in which the individual is inserted. With these questions as a backdrop, we elaborated the general and specific objectives, based on qualitative research as a methodological procedure, through surveys of primary sources, bibliography, documentary research, discourse analysis and comparative analysis. With the development of this research, we show a path as an instrument to understand how the filmic image shows places and socio-spatial formation, we inter-relate the possibilities of knowledge of the filmic work with the theoretical support of the Geography discipline, to contribute to the acquisition and construction of geographic knowledge. With this thesis, the result is to show the importance of broadening our perspective and the ways of building knowledge through filmic language, to understand the relationship between the theme of this research and the theme of justice, from a regional and national perspective.